Green finance in the United States of America, United Kingdom and Russian Federation: practice analysis - T. A. Gorbacheva; K. G. Bunevich (Управление)
Now, when the world economy is gradually transforming into a low-carbon one, the criterion of sustainable development of the green economy is becoming an increasingly decisive factor in the competitiveness of the state. Another aspect of relevance is the fact that aggressive business development, especially in terms of lending and investment, often opposes environmental protection issues. The purpose of this article is to study the practice of green finance in developed countries and identify development prospects in the Russian Federation. The methods of system and critical analysis, as well as graphical method were used in the work. It is revealed that foreign developed countries are actively improving legislation and introducing mechanisms of green financing. These processes do not always occur smoothly, it takes time to adapt and develop them, but there are more and more green financial instruments, the global financial system is gradually changing. It has been established that the processes of green energy transfer should have a steady but smooth character, otherwise there is always a risk of getting a completely unexpected negative result. It has been revealed that Russia has all the necessary resources to build a new, more environmentally friendly economy through green financing. But the transition to sustainable development, improvement of infrastructure and environmentally friendly industries is impossible without the active intervention of the state and changes in the self-consciousness of Russians.